Eliminating the isoleucine biosynthetic pathway to reduce competitive carbon outflow during isobutanol production by Saccharomyces cerevisiae. Issue 1 (December 2015) - Ida, Kengo; Ishii, Jun; Matsuda, Fumio; Kondo, Takashi; Kondo, Akihiko
Abstract Background Isobutanol is an important biorefinery target alcohol that can be used as a fuel, fuel additive, or commodity chemical. Baker's yeast, Saccharomyces cerevisiae, is a promising organism for the industrial manufacture of isobutanol because of its tolerance for low pH and resistance to autolysis. It has been reported that gene deletion of the pyruvate dehydrogenase complex, which is directly involved in pyruvate metabolism, improved isobutanol production byS. cerevisiae . However, the engineering strategies available forS. cerevisiae are immature compared to those available for bacterial hosts such asEscherichia coli, and several pathways in addition to pyruvate metabolism compete with isobutanol production. Results The isobutyrate, pantothenate or isoleucine biosynthetic pathways were deleted to reduce the outflow of carbon competing with isobutanol biosynthesis inS. cerevisiae . The judicious elimination of these competing pathways increased isobutanol production.ILV1 encodes threonine ammonia-lyase, the enzyme that converts threonine to 2-ketobutanoate, a precursor for isoleucine biosynthesis.S. cerevisiae mutants in whichILV1 had been deleted displayed 3.5-fold increased isobutanol productivity. The ΔILV1 strategy was further combined with two previously established engineering strategies (activation of two steps of the Ehrlich pathway and the transhydrogenase-like shunt), providing 11-fold higher isobutanol productivity as compared to the parent strain. The titer and yield of this engineered strain was 224 ± 5 mg/L and 12.04 ± 0.23 mg/g glucose, respectively. Conclusions The deletion of competitive pathways to reduce the outflow of carbon, includingILV1 deletion, is an important strategy for increasing isobutanol production byS. cerevisiae .